Triadic patterns across classical and popular music corpora: stylistic conventions, or characteristic idioms?. Issue 2 (4th May 2021) - Sears, David R. W.; Forrest, David
Abstract : Many musical traditions – from Western art, to popular and commercial – organize pitch phenomena around a referential pitch class (or tonic ) and feature triads and seventh chords. As a result, triadic progressions associated with one tradition sometimes resurface in others. How, then, are we to distinguish between the conventional harmonic patterns that span several time periods, and the characteristic idioms that delimit a single period? This essay presents a comparative study of triadic progressions in four data sets comprised of expert harmonic annotations: Annotated Beethoven Corpus (ABC), Theme and Variation Encodings with Roman Numerals (TAVERN), Rolling Stone-200 (RS-200), and McGill Billboard (Billboard). Using methods for counting, filtering, and ranking multichord expressions, we reveal conventional and characteristic progressions and examine broad trends over time. We also include an accompanying standalone application that allows users to adjust various stages of the model pipeline and export the data for further exploration and analysis.